Sistem Pengurusan Kualiti ISO 9002 di Sekolah : Hubungkait Status Pelaksanaan dengan Kualiti dan Produktiviti Guru - Ismail, Hj. Abdullah (1999)
The aim of the study is to see the relationship between the application status of ISO 9000 Quality Management System in the school with the quality and productivity of teachers (QPT). This study is an early exploratory study in the form of a case study. The orientation of the study is to look at the differences of the dimensions of the quality and productivity of teachers with regards to 3 school systems, that is, School With ISO 9002 Certification (known as Gl School), School In The Process Of Achieving The ISO 9002 Certification (G2 School), and School Without the ISO 9062 system. This case study is carried out in the Perks State, as two of the subjects, Gl and G2 are in that state. The instrument used to measure the quality and productivity of teachers was developed by Rahmah Yusak (1997). The instrument used for this study is the school’s administrators version. The result shows that the School Without ISO 9002 (G3) has a positive and high mean score than the School In The Process of Achieving ISO 9002 (G2), and also the School With ISO 9002 Certification (Gl), The dimensions in Gl that obtain high means were discipline, good morals, commitment, teamwork, and management. For G2 School, highly valued dimensions were good morals, discipline, commitment, teamwork, and management. Whereas G3 School, the dimensions that preceeded others were discipline, good morals, teamwork, commitment, and proactive. The research had fulfilled the purpose and objective where the comparison between the three different application status of ISO 9002 in the schools was contrasted in the dimensions of the quality and productivity of teachers. As a conclusion, the three schools with different status of the application of the ISO 9000 system, have a high quality dan productivity of teachers in the evaluation of the schools’ administrators.